Perubahan Kekuasaan Presiden di Indonesia - P ANTHONIUS SITEPU (Universitas Sumatera Utara, 2010)
Since independence August 17, 1945 to the present President of the Republic of Indonesia has been changing. In this period the power of the president of Indonesia has also experienced the ups and downs. The study looks at the phenomenon of tidal power is the President of Indonesia to the scope just to see and compare the phenomenon of power, President Soekarno and Presi-dent Soeharto. The results show if the period of Sukarno's power throughout the power centered on the president, during the Soeharto era, too. Both the authority of President Soekarno and President Soeharto's rule are both supported by the constitution so that it can be said as a con-stitutional dictator. Can be said to be substantively and procedural powers in the hands of Pres-ident Sukarno and Suharto was perfect. Both also managed to become the center of power and stick to most existing political elite. Thus the historical record in the history of presidential powers Indonesia's political system in the era of President Sukarno and Suharto's power is the history of executive dominance.Keywords: Executive dominance, Political elite, Constitutional dictator.